Law Making Process in Health Law: Political Interests and the Influence of Advocacy of Each Organization - Rasyid, M. Akbarizan; Irwan, Rahmatiah; Pricellia Eka Putri, Putu Pipit; Zeki, Destri; Wulan Dary, Alfi (Journal of Law, Politic and Humanities, 2025)
This research aims to analyze the law making process of the Health Law. The research method used is of the normative juridical type. The type of approach in research uses a statutory approach and an analytical approach. The sources of legal materials used are primary legal materials in the form of statutory regulations, and secondary legal materials in the form of relevant books and journals. The technique for collecting legal materials is carried out using document study techniques. After the legal materials are collected, the legal material analysis technique is carried out using descriptive techniques. The research results show that the law making process for the Health Law in Indonesia is influenced or cannot be separated from the interests of the political actors behind it. This is influenced by claims from actors who approve or are pro for the Health Law, and counter claims from actors who do not agree with the formation of this Health Law.